2011
DOI: 10.2135/cropsci2010.03.0129
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL Associated with Traits Affecting Grain Yield in Chickpea (Cicer arietinum L.) under Terminal Drought Stress

Abstract: The aim of this study was to evaluate a set of recombinant inbred lines (RILs) for agronomic and physiological traits under drought conditions and to locate quantitative trait loci (QTL) associated with them. This study used a RIL population derived from a cross between drought tolerant (ILC 588) and susceptible (ILC 3279) genotypes. The population consisting of 155 RILs was grown under drought conditions in the field at Tel Hadya, Syria, in 2006 and 2007 and at Breda, Syria, in 2007. A genetic map consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 40 publications
3
69
1
Order By: Relevance
“…Chr-I.B.3 is syntenic with M. truncatula chromosome 8 and chickpea chromosome 8 (Kaur et al 2014). Three flowering QTLs have been detected on M. truncatula chromosome 8 (Pierre et al 2008) and two on chickpea chromosome 8 (Rehman et al 2011;Varshney et al 2014). Sixteen flowering related genes have been identified on M. truncatula chromosome 8 by Kim et al (2013), including the photoperiod pathway genes: Casein kinase alpha 1 (CKA1); Casein kinase II, alpha chain 2 (CKA2); and Chryptochrome-interacting basic-helix-loop-helix 1 (CIB1).…”
Section: Masmentioning
confidence: 99%
“…Chr-I.B.3 is syntenic with M. truncatula chromosome 8 and chickpea chromosome 8 (Kaur et al 2014). Three flowering QTLs have been detected on M. truncatula chromosome 8 (Pierre et al 2008) and two on chickpea chromosome 8 (Rehman et al 2011;Varshney et al 2014). Sixteen flowering related genes have been identified on M. truncatula chromosome 8 by Kim et al (2013), including the photoperiod pathway genes: Casein kinase alpha 1 (CKA1); Casein kinase II, alpha chain 2 (CKA2); and Chryptochrome-interacting basic-helix-loop-helix 1 (CIB1).…”
Section: Masmentioning
confidence: 99%
“…ILB 938/2 had lower g s , lower stomatal density, and hence lower productivity, and when exposed to drought conditions it had less reduction in g s and less change in canopy temperature than Mélodie/2. In chickpea, genotypes that maintained higher g s and kept cooler canopy temperature under drought stress conditions during the reproductive period performed better than those that did not (Rehman et al 2011). In faba bean, it was shown that accessions with higher stomatal density had less resistance to water stress (Ricciardi 1989).…”
Section: Variation and Association Between Studied Traitsmentioning
confidence: 99%
“…In terms of abiotic stresses, Vadez and colleagues (2012) at ICRISAT identified QTLs for salinity tolerance and inferred that tolerance is associated with earliness in chickpea. Although efforts were made to understand drought tolerance (Rehman et al 2011;Hamwieh et al 2013), the studies aimed to understand the performance of agronomic or physiological traits. Recent research endeavours at ICRISAT by Varshney et al (2014b) may eventually lead to a comprehensive understanding of drought tolerance in chickpea.…”
Section: Trait Mappingmentioning
confidence: 99%